Eicosapentaenoic Acid Blocks Cyclosporine A-Induced Pancreatic Dysfunction but not Immunosuppression - Takashi Majima, Kazuki Sasaki, Hiroshi Ohara, Norio Takahashi (Journal of Applied Pharmaceutical Science, 2017)
Cyclosporine A (CsA) is a widely used immunosuppressant in transplantation medicine. However, it has oxidative stress-induced side effects, including nephrotoxicity, hypertension, dyslipidemia, and glucose intolerance; particularly, post-transplant diabetes mellitus, accompanied by alterations of pancreatic islet cells, has been reported as a major adverse event. Recent research indicates that omega-3 polyunsaturated fatty acids, such as eicosapentaenoic acid (EPA), have antioxidant and anti-inflammatory activities. However, protective effects of EPA against CsA-induced alterations of pancreatic islet cells and hyperglycemia have not been examined in long-term administration of CsA in rats. The aim of this study was to determine whether EPA can abrogate these negative effects by assessing pancreatic islet cell dysfunction, vacuolation, and hyperglycemia in rats continuously treated with CsA. These pathologies were significantly improved by concomitant administration of EPA. Importantly, EPA did not affect the immunosuppressive effects of CsA, as evidenced by nuclear translocation of nuclear factor of activated T-cells in pancreatic tissue in response to lipopolysaccharide stimulation. Thus, EPA can be used to prevent CsA-induced oxidative stress and/or inflammation in pancreatic islets. Our data also suggest that EPA can be used in conjunction with CsA to mitigate its harmful side effects while preserving its immunosuppressant properties in transplant patients.
Keywords: CsA, islet cell vacuolation, glucose intolerance, EPA, NFAT.